Morphology and Magnetic Properties of Ferriferous Two-Phase Sodium Borosilicate Glasses - Naberezhnov, Alexander (Hindawi Publishing Corporation, 2014)
This contribution is devoted to the study of morphology and magnetic properties of sodium borosilicate glasses with different concentrations (15, 20, and 25 wt.%) of α-Fe(2)O(3) in an initial furnace charge. These glasses were prepared by a melt-quenching method. For all glasses a coexistence of drop-like and two-phase interpenetrative structures is observed. The most part of a drop structure is formed by self-assembling iron oxides particles. All types of glasses demonstrate the magnetic properties and can be used for preparation of porous magnetic matrices with nanometer through dendrite channel structure.